PERANCANGAN SISTEM STOCK BARANG BERBASIS WEB MENGGUNAKAN METODE WATERFALL DI RAFIZA FRIED CHICKEN - Ayyash Umar Kholid; Muhammad Farhan; Satria Agung Wibowo; Saprudin (shofanah Media Berkah, 2024)
This article presents the design and implementation of a web-based stock system for Rafiza Fried Chicken using the Waterfall method. This project aims to improve the efficiency and accuracy of the stock management process. This system was developed to facilitate inventory tracking, reduce errors, and improve decision-making capabilities. The methodology used includes requirements analysis, system design, implementation, testing and maintenance. The results show significant improvements in stock management and operational efficiency.